Leader Humility and Knowledge Sharing Intention: A Serial Mediation Model - Nguyen, Diep T. N.; Teo, Stephen T. T.; Halvorsen, Beni; Staples, Warren (Frontiers in Psychology, 2020)
Purpose This paper examines the influence of leader humility on knowledge sharing intention. Drawing on social exchange theory (SET), we test the direct and indirect mechanisms to explain the influence leader humility has on knowledge sharing intention. Design/Methodology/Approach A two-wave, time-lagged field study was conducted. We surveyed 252 professional employees from Australia. Findings Results show a significant direct, positive association between leader humility and knowledge sharing intention. While leader humility had a direct, positive association with affective trust in supervisor and work engagement, it did not directly impact on organizational citizenship behaviors directed toward the individual (OCB-I). There were three SET-related, serial mediators in the relationship between leader humility and knowledge sharing intention. These were affective trust, work engagement, and OCB-I. Research Limitations/Implications Future studies should collect multi-source data such as peers’ or supervisors’ ratings of the focal respondents’ work engagement, OCB-I, and knowledge sharing behaviors to augment single-source data. Future studies could adopt an affect theory of social exchange to further explore the relationships tested in this study. Originality/Value This study contributes to the affect SET and knowledge management literature on how leadership behaviors impact the intention to share knowledge. Our study highlights the preference of the willingness to share knowledge with their co-workers is mediated by affective trust in their immediate supervisors, work engagement, and OCB-I that are equally important as treating their subordinates with humility.